The Role of Financial Technology in Increasing Financial Access - Caturadina Darnida, Yondi; Haryono, Andri; Nurriqli, Arifia (Journal of Management, 2024)
Financial access plays an essential role in establishing financial inclusion and economic welfare. The purpose of this study is to examine the impact of financial literacy, regulatory, infrastructure, and adaptation variables on financial access. To assess the association between independent factors and Financial Access, this study employs a quantitative technique, namely a linear regression model. The findings indicate that Financial Literacy has a substantial impact on Financial Access (t = 2.862, p = 0.005). In contrast, the factors Adaptation, Regulatory, and Infrastructure had no significant effect on Financial Access (p > 0.05). The total regression model is significant (F value = 27.019, p = 0.000), accounting for 53.2% of the variation in Financial Access (R Square = 0.532). The measurement apparatus had a Cronbach's Alpha of 0.899, indicating excellent internal consistency. Financial literacy is demonstrated to be a key determinant in improving financial access, but adaptation, regulatory, and infrastructure variables have no meaningful contribution in the context of this model. The applied regression model effectively explains the majority of the variation in Financial Access, with the instruments demonstrating great reliability and validity. The findings give valuable insights for policymakers and practitioners in enhancing financial access.